1991
DOI: 10.1136/thx.46.11.839
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pulmonary aspergilloma with itraconazole.

Abstract: In a 12 month open study of itraconazole in pulmonary aspergilloma nine patients received oral itraconazole 200 mg daily for six months followed by further itraconazole or observation for a further six months. There was no change in the serum IgG specific for Aspergillus fumigatus (mean (SE) change -4% (10%)) or symptoms of chronic cough and haemoptysis. In two of the three patients who continued treatment beyond six months symptoms and radiographic appearances improved and a temporary reduction in A fumigatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
4

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 7 publications
1
43
0
4
Order By: Relevance
“…Occasionally patients have a complete response [136][137][138]. In one study, significant itraconazole levels within the aspergilloma cavities were demonstrated after using the standard dose of itraconazole (100-200 mg?day -1…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Occasionally patients have a complete response [136][137][138]. In one study, significant itraconazole levels within the aspergilloma cavities were demonstrated after using the standard dose of itraconazole (100-200 mg?day -1…”
Section: Treatmentmentioning
confidence: 99%
“…According to the recent statement of the American Thoracic Society for treating fungal infections in adults [123], the duration of IPA therapy should be individualised to the Continuation therapy: voriconazole or itraconazole [122,123] Salvage therapy: echinocandin or posaconazole [125][126][127] Chronic necrotising aspergillosis Voriconazole [120,123] Alternative therapy: itraconazole [128,129] Severe cases: intravenous voriconazole or liposomal amphotericin B [123,128,130] Consider surgical resection [130] Aspergilloma Observation [123] Bronchial artery embolisation [131] Surgical resection [132][133][134][135] Consider itraconazole [136][137][138] Allergic bronchopulmonary aspergillosis Corticosteroids [139][140][141][142] Itraconazole or voriconazole as steroid-sparing agents [143][144][145][146] Surgical resection has generally a limited role in the management of patients with IPA, but it becomes important in cases with invasion of bone, burn wounds, epidural abscesses and vitreal disease [123]. It should also be considered in cases of massive haemoptysis, pulmonary lesions close to the great blood vessels or pericardium, or residual localised pulmonary lesions in patients with continuing immunosuppression or those who are expected to have immunosuppressive therapy in the future.…”
Section: Treatmentmentioning
confidence: 99%
“…(iv) Chromatography. The chromatograph consisted of a Waters model 6000A pump connected to a C18 guard column and a steel cartridge (100 mm by 4.5 mm inside diameter) containing Hypersil octyldecyl silane (particle size, 3 ,um) (Alltech, Carnforth, United Kingdom). The mobile phase consisted of water-acetonitrile (40:60) containing 0.03% diethylamine; it was adjusted to pH 7.8 with dilute orthophosphoric acid and then filtered and degassed under reduced pressure before use.…”
mentioning
confidence: 99%
“…An assessment made on the use of triazole drugs is also difficult because fluconazole itself, especially with the low dose they used, would not be expected to be of benefit for PA. The doses used of itraconazole were also below what would be considered therapy for PA [5]. …”
Section: Invited Commentarymentioning
confidence: 99%